Effect of Relaxation Technique in Breathing on the Pain Level of Dysmenorhea’s Pain in Teenage Girl - Agustina Simanangi Pamowa; Ratih Wirapuspita Wisnuwardani (Indonesian Journal of Global Health Research, 2024)
The technique of deep breathing relaxation can reduce the intensity of pain and improve pulmonary ventilation and increase blood oxygenation so the young man can adapt to pain during dysmenorrhea. This study aimed to examine the association between deep breathing relaxation techniques and the level of dysmenorrhea pain in adolescent girls at SMPN 6 Samarinda City. Quasi experimental with one group pre-test and post-test model. The non-probability sampling was applied with 40 respondents. Wilcoxon test was used to analyse data in this study. there was a significant association between deep breathing relaxation techniques and the level of dysmenorrhea pain in adolescent girls at SMPN 6 Samarinda City (p=0,0001). The deep breathing relaxation technique has an effect on the level of pain and can be used as one of the pain adaption techniques.